Development and reliability testing of a qualitative observational rating system for individuals with brachial plexus injury performing functional capacity evaluation tests - Tallie M. J. van der Laan; Sietke G. Postema; Corry K. van der Sluis; Michiel F. Reneman (PLoS ONE, 2026)
Background Individuals with brachial plexus injury may be more prone to develop musculoskeletal complaints, due to compensatory strategies. Quantifying compensatory strategies of these individuals may help to minimize the use of dysfunctional compensatory strategies and prevent musculoskeletal complaints. Purpose To develop and to explore the feasibility of an observational rating system for rating postures and movements of the shoulders and trunk in individuals with brachial plexus injury during the performance of the functional capacity evaluation one-handed-individuals (FCE-OH) and to explore the interrater and intrarater reliability of this rating system. Study design Psychometric study including development and reliability testing. Methods Individuals with brachial plexus injury (n = 15) and able bodied controls (n = 21) were videotaped during the performance of five FCE-OH tests. Abnormal shoulder and trunk movements and postures were identified. The rating system was developed pilot tested and adjusted. The interrater and intrarater reliability of the final draft were determined. Sixteen raters performed two rating sessions, two weeks apart and rated 40 video fragments. Absolute percentages of agreement, kappa (ĸ) and 95% confidence intervals (CI) were calculated. Feasibility was explored using a questionnaire. Results The interrater reliability of the rating system was: first session ĸ = 0.48, 95%CI = 0.36–0.60; second session ĸ = 0.59, 95%CI = 0.45–0.72. The intrarater reliability was ĸ = 0.64, 95%CI = 0.50–0.70. Half of the raters agreed that the system was easy to use in clinical practice. Conclusions A rating system for measuring postures and shoulder and trunk movements of individuals with brachial plexus injury was developed. The reliability appeared to be sufficient when the system was applied by the same rater. The interrater reliability was moderate for both rating sessions. The reliability of both overhead lifting tests of the FCE-OH was low. Variation in movement patterns due to differences in the remaining function of the affected arm may have caused difficulties in rating.